PEMANFAATAN LIMBAH FASHION (FAST FASHION WASTE) MENJADI PRODUK ECO-FASHION BERBASIS EKONOMI SIRKULAR UNTUK MENDORONG GAYA HIDUP BERKELANJUTAN DI KALANGAN MAHASISWA - Riswan Efendi; Muhammad Ilham; Eryana Eryana; Susilawati Susilawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The creative economy is a strategic sector in driving local economic growth. Bengkalis Regency has great potential in developing the creative economy, especially through unique local products. However, the limited knowledge and skills of business actors are the main challenges. This study aims to design and implement a local product-based entrepreneurship training program in Bengkalis District. The method used is a participatory approach by involving local business actors in every stage of training. The results show a significant increase in participants' understanding of business management, digital marketing, and product innovation. This program is expected to be a model for empowering the creative economy in other areas.